Integration of Al-Ghazali’s Moral Thought and Nurcholish Madjid’s Intellectualism in the Development of Islamic Religious Education in the Contemporary Era: Integrasi Pemikiran Moral Al-Ghazali dan Intelektualisme Nurcholish Madjid dalam Perkembangan Pendidikan Agama Islam pada Era Kontemporer - Choiriyah, Is'ad Ummul; Permadi, M. Syafrany Surya; Fahmi, Muhammad (Universitas Muhammadiyah Sidoarjo, 2026)
This study looks at how Nurcholish Madjid's intellectualism and Imam Al-Ghazali's moral philosophy have been incorporated into the evolution of Islamic Religious Education (PAI) in the modern day. The problem brought up is the Islamic educational system's duality between morality and reason, which results in a poor balance between the development of spiritual character and critical thinking abilities. The goal of this research is to offer an integration model between tazkiyat al-nafs (soul purification) and the intellectualism of tauhidi (reason based on divine principles). A literature study is carried out using a qualitative method by examining the original and secondary works of both figures as well as pertinent research findings. The results show that Al-Ghazali emphasizes the formation of morality through heart purification. The results show that although Al-Ghazali emphasizes the formation of morality through heart purification, Nurcholish Madjid emphasizes the importance of freedom of thought within the context of tauhid. When the two are combined, an Islamic educational paradigm is created that strikes a balance between faith and knowledge, ethics and logic, and dhikr and fikir. This methodology offers an innovative approach to the revitalization of holistic and transformative PAI and helps create a generation of Muslims who are morally upright, logical, and able to deal with contemporary issues.